Visualisation of the insertion of a membrane for the treatment of preterm rupture of fetal membranes using a synthetic model of a pregnant uterus. (August 2018) - Roman, Sabiniano; Hillary, Christopher; Narice, Brenda; Bullock, Anthony J; Anumba, Dilly OC; MacNeil, Sheila
Preterm premature rupture of fetal membranes is a leading cause of preterm delivery. Preterm labour can compromise fetal survival, and even if a pregnancy affected by preterm premature rupture of fetal membrane continues, major complications associated with leakage of amniotic fluid and risk of infection can affect the normal development and survival of the baby. There are limited management options for preterm premature rupture of fetal membrane other than delivery of the baby if ascending infection (chorioamnionitis) is suspected. We have previously reported the development and characterisation of an implantable membrane with the aim of using it to occlude the internal os of the cervix, in order to prevent amniotic fluid loss, allow fluid reaccumulation and reduce the risk of chorioamnionitis. For this, an electrospun biocompatible and distensible bilayer membrane was designed with mechanical properties similar to the human amniotic membrane. In this study, we consider the effects of sterilization on the membrane, how to insert the membrane and visualise it using routine clinical methods. To do this, we used e-beam sterilisation and examined the ability of the membrane to adhere to ex vivo human cervical tissues. We also studied its insertion into a custom-synthesised model of a 20-week pregnant uterus and imaged the membrane using ultrasound. Sterilisation produced minor effects on physical and mechanical properties, but these did not affect the capacity of the membrane to be sutured or to provide a fluid barrier. We demonstrated that fibrin glue can successfully adhere the bilayer membrane to cervical tissues. Finally, we demonstrated that the membrane can be inserted through the cervix as well as visualized in place using ultrasound imaging and an endoscope. In summary, we suggest this membrane is a candidate for further development in an appropriate animal model, supported by appropriate imaging, to precede possible future human studies if judged to demonstrate satisfactory safety and efficacy profiles.